In vitro effects of famotidine and ranitidine on lower esophageal sphincter tone in rats - Mahmut ÖZER; Mustafa DUMAN; Şükrü TAŞ; Yeliz DEMİRCİ; Muhammet Fatih AYDIN; Enver REYHAN; Ali Emre ATICI; Erdal Birol Bostancı; Musa AKOĞLU; Ece GENÇ (Turkish Journal of Gastroenterology, 2019)
-